Sistem Manajemen Restoran X Berbasis Rich Internet Application - Stella Fania; Robby Tan (Maranatha University Press, 2015)
A restaurant is inseparable from the role of information systems. Restaurant X needs a system for displaying menu interactively, ordering foods, payment, table reservation, etc. The system is required to minimize errors and maintain coordination between the waiters, chefs, and cashiers. Users for this system are owners of the restaurant, customers, waiters, chefs, and cashiers. This system is made in two different platforms. Dekstop version will be used by owners, customers, chefs, and cashiers while the mobile version will be used by waiters. Adobe Flex is used for implementing Rich Internet Application (RIA) for this system while MySQL is used for storing its datas. Implementation of this system is proven to improve the quality of care and minimize human error in the restaurant X. Keywords: Menu, Order, Restaurant